Modeling the kinetics of whey protein hydrolysis brought about by enzymes from Cynara cardunculus - Barros, Rui M. (2011)
The purpose of this research work was to study the proteolytic activity of aqueous crude extracts of flowers of the plant Cynara cardunculus on the major whey proteins, namely, â-lactoglobulin (â-Lg) and R-lactalbumin (R-La). These extracts, containing a mixture of cardosins A and B (i.e., two distinct aspartic proteases), have been employed for many years in traditional cheese-making in Portugal and Spain. Cow’s milk sweet whey was incubated for up to 24 h at various ratios of addition of crude enzyme extract, under controlled pH (5.2 and 6.0) and temperature (55 °C). The samples collected were assayed by gel permeation chromatography and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. A mechanistic model was proposed for the kinetics of the hydrolysis process, which is basically a double-substrate, double-enzyme Michaelis-Menten rate expression; the kinetic parameters were estimated by multiresponse, nonlinear regression analysis. The best estimates obtained for the specificity ratio (i.e., kcat/Km) of each cardosin within the mixture toward each whey protein indicated that said aspartic proteases possess a higher catalytic efficiency for R-La (0.42- 4.2 mM-1âs-1) than for â-Lg (0-0.064 mM-1âs-1), at least under the experimental conditions used. These ratios are below those previously reported for caseins and a synthetic hexapeptide. Cardosins are more active at pH 5.2 than at pH 6.0 and (as expected) at higher enzyme-to-substrate ratios.